Economic Empowerment of the Scrap Carpenter Community Based on Asset-Based Community Development in Kedunglosari Village, Jombang - Muhammad Nasrul Waton; Fathoni Fathoni; Abdullah Asyiq (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract:The problem of waste management and the marginal economic conditions of the scrap collector community are the main background of this community service. The program aims to improve the economic welfare of the scrap collector community in Kedunglosari Village, Tembelang District, Jombang Regency through an Asset-Based Community Development (ABCD) approach. The method used includes five ABCD stages (Discovery, Dreaming, Design, Define, Delivery) with asset identification activities, Focus Group Discussions (FGDs), scrap sorting and processing training, and the formation of the Joint Business Group (KUB) "Rosok Sejahtera". The subjects of mentoring were 15–20 heads of scrap collector families. The results showed an increase in average daily income of 30–40% (from Rp40,000–Rp60,000 to Rp60,000–Rp90,000), strengthening social solidarity, reducing negative stigma, and reducing the volume of village waste. The ABCD approach has proven effective in encouraging economic independence of the informal sector based on local assets. Recommendations are directed at sustainable support from the village government.